Sustainable Wastewater Treatment Technology for Rural Communities - Ahmed, Yousra (AUC Knowledge Fountain, 2021)
Egypt is considered the country with the largest population in the Middle East Region. It is also expected to have the most significant population increase. The main objective of the present research was to develop a sustainable and effective wastewater treatment technology based on locally available materials such as sand and fabric in the treatment process. From the results obtained from the different experimental runs, it can be concluded that the use of fabric-aided sand filters achieves significant removal efficiency, especially in terms of COD and TSS. The results indicated the technical feasibility of utilizing different fabric materials with nylon identified as the optimum fabric. Furthermore, the results indicated that increasing the number of fabric layers enhanced the system’s performance. The results showed that the best number of layers ranges between five and ten. The system also showed tolerance of variable pollutants loads, with better performance under higher influent pollutants concentrations. The majority of the removal took place at the fabric sheets. The application of the Rapid Sustainability Screening (RSS) showed that it captured the key factors associated with wastewater treatment in Egypt. This simple tool can be used by developer and decision makers as a first screening step for the selection of optimum alternatives. It can be also used for assessing the existing treatment units and identify areas of improvement to enhance their sustainability. The sustainability assessment of the proposed fabric aided filter indicated that it is environmentally, socially, and economically sustainable.